E-procurement on Organizational Performance in Uganda: A Case Study the Norma Freight Service U Limited Kampala - Mugeni Benjamin (Uganda Christian University, 2024)
This study examines the effectiveness of e-tendering, e-catalog management, and e-purchase order automation at Norma Freight Service Limited in Kampala. Utilizing a survey of 320 respondents and employing SPSS for data analysis, both descriptive and inferential statistics were applied to identify critical factors influencing these e-procurement processes. The findings highlight that proper governance and training significantly predict successful e-tendering implementation, with governance showing a stronger effect. Effective e-catalog management is influenced by system usability and data accuracy, with usability having a slightly higher impact. For e-purchase order automation, process efficiency and error reduction are crucial, with efficiency being the more significant factor. Based on these results, the study recommends enhancing governance structures, improving training programs, designing user-friendly systems, ensuring data accuracy, optimizing processes, and implementing error minimization measures. These improvements are expected to enhance e-procurement efficiency, reduce errors, and improve overall organizational performance at Norma Freight Service Limited. The research concludes by discussing the practical implications and suggesting directions for future studies to further explore and enhance the effectiveness of e-procurement systems.